Democratic Republic of the Congo : Staff-Monitored Program and Request for Disbursement Under the Rapid Credit Facility; Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of the Congo. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses The Democratic Republic of the Congo's Staff-Monitored Program and Request for Disbursement Under the Rapid Credit Facility. The economic environment remains challenging and vulnerable to shocks. Real gross domestic product growth is projected to decelerate to 4.5 percent in 2019 from 5.8 percent in 2018. The recent fall in commodity prices, new spending initiatives, and looser spending oversight during the political transition period have led to a weaker fiscal position mostly financed by the central bank. In this context, international reserves have fallen to critically low levels creating urgent balance of payment needs. The new government is committed to implementing measures and reforms that would strengthen macroeconomic stability, reinforce international reserves, address issues related to poor governance, a difficult business environment, and pervasive poverty. Authorities also intend to boost domestic revenue by restoring the functioning of the value-added tax and enforcing the personal income tax, while improving mining revenue forecasting. In addition, the government intends to introduce strict spending caps, increase the effectiveness of monetary policy, and foster inclusive growth and private sector development including through infrastructure projects and free basic education.